2023
DOI: 10.1021/acs.jmedchem.2c02107
|View full text |Cite
|
Sign up to set email alerts
|

Quinazoline-2-Carboxamides as Selective PET Radiotracers for Matrix Metalloproteinase-13 Imaging in Atherosclerosis

Abstract: Matrix metalloproteinase-13 (MMP-13) plays a critical role in the progression of unstable atherosclerosis. A series of highly potent and selective MMP-13 inhibitors were synthesized around a quinazoline-2-carboxamide scaffold to facilitate radiolabeling with fluorine-18 or carbon-11 positron-emitting nuclides and visualization of atherosclerotic plaques. In vitro enzyme inhibition assays identified three compounds as promising radiotracer candidates. Efficient automated radiosyntheses provided [ 11 C]5b, [ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Ex vivo aortic autoradiography and competition studies revealed that [ 18 F]20 (Figure 3) specifically binds to MMP-13 within atherosclerotic plaques and localizes to lipid-rich regions. 37 GPR119 is a G protein-coupled receptor, highly expressed in the pancreas, that regulates secretion of insulin and incretins, and is a target for drug development to treat diabetes. Measuring GPR119 levels in vivo could significantly advance 3+ , demonstrating quantitative radiochemical yields (RCYs) within 10 min at ambient temperature and achieving notably high molar activities.…”
Section: Imaging and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo aortic autoradiography and competition studies revealed that [ 18 F]20 (Figure 3) specifically binds to MMP-13 within atherosclerotic plaques and localizes to lipid-rich regions. 37 GPR119 is a G protein-coupled receptor, highly expressed in the pancreas, that regulates secretion of insulin and incretins, and is a target for drug development to treat diabetes. Measuring GPR119 levels in vivo could significantly advance 3+ , demonstrating quantitative radiochemical yields (RCYs) within 10 min at ambient temperature and achieving notably high molar activities.…”
Section: Imaging and Therapymentioning
confidence: 99%
“…The manuscript by Rotstein et al reported the synthesis and preclinical evaluations of selective matrix metallo­proteinase-13 (MMP-13) PET radio­tracers for the early detection of unstable plaques that are risk factors for acute ischemia. Ex vivo aortic auto­radiography and competition studies revealed that [ 18 F] 20 (Figure ) specifically binds to MMP-13 within athero­sclerotic plaques and localizes to lipid-rich regions …”
Section: Other Radiopharmaceuticals For Imagingmentioning
confidence: 99%